Sources of income subject to tax in the Iraqi Income Tax Law No.113 of 1982 (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The tax is a financial amount collected from the taxpayer for the account of the public treasury.. and is the cornerstone of the close bond between members of the community and the country in which they live , as income tax is imposed on the profits and revenues achieved by people and often the constitution of most contemporary countries stipulate that the legislator is obligated to determine the sources of revenues and profits subjected to tax. Because the tax has a serious impact on people’s money because it is exposed to that money through direct deduction . Therefore, we note that the applicable income Tax Law stipulated that in order income to be subject to tax , it must be derived from one or more of the income sources stipulated in Article Two of it.